2017
DOI: 10.1038/s41467-017-01157-4
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale water collection of bioinspired cavity-microfibers

Abstract: Large-scale and high-efficient water collection of microfibers with long-term durability still remains challenging. Here we present well-controlled, bioinspired spindle-knot microfibers with cavity knots (named cavity-microfiber), precisely fabricated via a simple gas-in-water microfluidic method, to address this challenge. The cavity-microfiber is endowed with unique surface roughness, mechanical strength, and long-term durability due to the design of cavity as well as polymer composition, thus enabling an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
172
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 27 publications
0
172
0
Order By: Relevance
“…Another study demonstrated the high efficiency of spider-weblike meshes ( Figure 1C) assembled by low-cost cavity-microfibers in directional water transportation. 43 Frankly, these methods show great potential for collection efficiency improvement, but these studies were only conducted under controlled laboratory conditions and still need more field tests to verify their true performance.…”
Section: Modern Awgsmentioning
confidence: 99%
“…Another study demonstrated the high efficiency of spider-weblike meshes ( Figure 1C) assembled by low-cost cavity-microfibers in directional water transportation. 43 Frankly, these methods show great potential for collection efficiency improvement, but these studies were only conducted under controlled laboratory conditions and still need more field tests to verify their true performance.…”
Section: Modern Awgsmentioning
confidence: 99%
“…With increasing population and degrading environment, freshwater scarcity is becoming a major global challenge . As atmospheric water is estimated to be ≈10% of all fresh water on earth, water harvesting from air is attracting significant attention with several strategies such as fog water capture and dewing collection . Recently, solar‐driven atmospheric water generator based on a sequential adsorption–desorption process is emerging as a promising option.…”
mentioning
confidence: 99%
“…Nevertheless, these approaches are largely limited either by the poor controllability of the morphology or by low reproducible ability and expensive equipment. Significant advances have been spurred in fiber generation as a result of progress in microfluidic platform, which can precisely manipulate small quantities of fluids within integrated microchannels . With the advantage of controllable fabrication, microfluidic systems allow facile assembly of fibers with desired geometries and multiple compartments .…”
Section: Microfluidics‐based Biomaterialsmentioning
confidence: 99%